(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the frequency of patients who develop acute adverse reactions to antisnake venom after receiving low dose subcutaneous adrenaline with those receiving only placebo. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Department of Medicine, Benazir Bhutto Hospital Rawalpindi from May 2019 to November 2019. Methods: Ethical approval for the study was sought from Institutional Research and Ethics Forum of RMU. After obtaining informed consent, all the patients with systemic envenomation were given 0.25m1 of 1:1000 adrenaline (cases) or placebo(control) subcutaneously into forearm immediately before starting ASV infusion. Patients were then monitored for acute adverse reactions. To compare the proportion of acute adverse reactions between two groups Pearson’s Chi-square test at 5% level of significance was applied. P- value of <0.05 was considered statistically significant. Results: Total patients in study were 60 which were equally divided into two groups i.e. Placebo and study group. The mean age of the patients was 35.87 ± 14.55 years. The gender distribution showed that 35 (58.3%) patients were from the male gender. Regarding the adverse reactions, 21 (35%) patients developed the acute reactions. There was significant difference among groups in terms of adverse reaction (05 (16.67%) in adrenaline group versus 16 (53.33%) in placebo group, p value was 0.003). Conclusion: The risk of adverse reactions due to asv is lower in group in which the low dose subcutaneous adrenaline was used as compared to placebo group. The data should be verified on larger scale study.